Competing Para-Sovereignties in the Borderlands of Europe. Issue 4 (2nd October 2017) - Johnson, Corey
ABSTRACT: This article is broadly concerned with how we conceptualise the geography of the tensions between the nominally stable orders of the modern state system against the turbulence of the past few decades in relation to that order, especially in the realm of border controls. Specifically, it considers the rescaling and relocation of border enforcement in the European Union in relation to state sovereignty. The article argues that existing "soft" conceptualisations of the EU's relationship to sovereignty and bordering—"shared, " "joint, " "multi-level, " "consociational"—are inadequate to understand the transformations of exercises of sovereign power in European borderlands. Instead, we are witnessing the emergence of competing para-sovereignties acting within the same spaces, with both traditional states and the incipient state-like EU fulfilling particular bit roles in realms that were traditionally viewed as the exclusive responsibilities of modern, sovereign, territorial states. This dynamic is made visible in recent years in observing individual humans negotiate and subvert the fluid political geographies of European border space. Examples are taken from the activities of the EU border agency Frontex in southeastern Europe.